Decision support system for inventory control using ABC analysis method at PT. MOD Indo Ungaran - Yoannes Romando Sipayung; Miski Aderisa (Institute of Computer Science (IOCS), 2023)
The ability to process data is to process raw data into useful information for users, in this case, PT. Mod Indo finds it difficult when making procurement decisions because there are factors that must be considered, namely the expenditure of goods, the need for goods, and the allocation of goods. The absence of a patented system causes some employees to frequently use estimates so that excess inventory often occurs for a long time which results in damage to goods. To realize better performance, it is necessary to build a decision support system in the supply of goods stock. This study aims to design and build a decision support system to help control inventory at PT. Indo mod. The system developed uses the programming language PHP and MySQL as a database, using the ABC Analysis Method which is a calculation of the distribution of classes based on the value of an item. In the study, testing 100 data on this system produced a cumulative 78.98% cumulative item group A category with 15 total items, 11.05% cumulative item B group with 10 total items, and item C group 9.97% cumulative 75 total goods. Classification of goods produces appropriate data, namely in the form of data that has the highest priority to be controlled. With this system, it can help PT Mod Indo to track, plan, and control inventory optimally, so that it can identify goods with fast, medium, and slow turnover, and can increase work efficiency and production for employees